Medication - Khan, Eman (Stimulus: A Medical Humanities Journal, 2023)
This is a collage of photographs of my medication. It's a glimpse into one of the toughest parts about being chronically ill, which is taking medication. There's a struggle and trial-and-error in finding the right medication that will provide even a small dent of relief. Dealing with side effects is an added burden. Trying to get insurance to approve life-saving medication is draining.